The Contribution of Intellectual Capital to Value Creation - Elena Shakina; Angel Barajas (Contemporary Economics, 2013)
This paper studies the marginal contribution of intellectual capital (IC) components to company value using a hedonic pricing framework. The ANOVA is used to identify group differences among different national markets and industries. Two models have been developed to reflect the time effect: one related to the immediate creation of value and another for the long term. As could be expected, the contribution of IC to companies' value creation differs significantly between countries and industries. Both models, short- and long-term, are significant and with a normal explanatory power. We have found both positive and negative coefficients. Human capital plays a critical positive role in value creation in the short term. Structural and relational capital becomes more relevant in the long term. However, in the long term, the results obtained regarding the effect of human capital are unclear.
Keywords: O12; L20; M21; J24; 330; intellectual capital; hedonic price; contribution; value creation; EVA; FGV